Genomics, evolution, and crystal structure of a new family of bacterial spore kinases - Scheeff, Eric D (Wiley Subscription Services, Inc., A Wiley Company, 2010)
Bacterial spore formation is a complex process of fundamental relevance to biology and human disease. The spore coat structure is complex and poorly understood, and the roles of many of the protein components remain unclear. We describe a new family of spore coat proteins, the bacterial spore kinases (BSKs), and the first crystal structure of a BSK, YtaA (CotI) from Bacillus subtilis. BSKs are widely distributed in spore-forming Bacillus and Clostridium species, and have a dynamic evolutionary history. Sequence and structure analyses indicate that the BSKs are CAKs, a prevalent group of small molecule kinases in bacteria that is distantly related to the eukaryotic protein kinases. YtaA has substantial structural similarity to CAKs, but also displays distinctive features that broaden our understanding of the CAK group. Evolutionary constraint analysis of the protein surfaces indicates that members of the BSK family have distinct clade-conserved patterns in the substrate binding region, and probably bind and phosphorylate distinct targets. Several classes of BSKs have apparently independently lost catalytic activity to become pseudokinases, indicating that the family also has a major noncatalytic function. Proteins 2010. © 2009 Wiley-Liss, Inc.